Na kung saan kapirasong kritika, mahigit isang dekada - Marasigan, Teo S.; University of the Philippines Press (Quezon City University of the Philippines Press, 2018)
On politics and popular culture in the Philippines.
Includes bibliographical references and index.
In Tagalog, with one article in English.
Keywords: Popular culture -- Philippines; Philippines -- Politics and government